Effect of Sweet Purple Potato Extract (Ipomoea batatas L) on Zebrafish (Danio rerio) by Diet Induced Obesity - Aswaty Nur; Yhusi Karina Riskawati; Edwin Widodo; Retty Ratnawati; Amirah Firdausy; Lydia Kusuma Dewi; Maria Karina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
The effect of a high-fat diet on zebrafish as an alternative experimental animal in studying lipid metabolism is not fully understood. In this research, sweet purple potato extract (SPPE) which has anthocyanin have used as an anti-obesity property. Zebrafish aged 8 mpf was divided into five groups: Non-DIO (control negative), DIO (Diet-Induced Obesity, control positive), and three experimental groups (DIO A, DIO B, DIO C). Each group consisted of five Zebrafish. All groups have been fed freshly hatched Artemia for 40 days where the Non-DIO’s amount was 5 mg Cyst/fish one time per day, and the other groups’ amount was 60 mg Cyst/fish three times per day. The experimental groups were exposed to sweet purple potato extract three times per day by different SPPE doses: DIO A by 80 ppm, DIO B by 120 ppm, and DIO C by 160 ppm. The results show that there was no significant difference between the positive control group and the experimental groups in term of feeding intake, BMI, blood glucose, and total cholesterol. However, based on molecular parameters, there was a declining trend on PPAR-γ level, although, the adiponectin level remained stable. We suggest that anthocyanin does not affect feed intake, BMI, blood glucose level, cholesterol, and expression of PPAR-γ and adiponectin of zebrafish with diet-induced obesity.